Complete Pathologic Responses With Immunotherapy in Metastatic Renal Cell Carcinoma: Case Reports - Tucker, Matthew D.; Beckermann, Kathryn E.; Gordetsky, Jennifer B.; Giannico, Giovanna A.; Davis, Nancy B.; Rini, Brian I. (Frontiers in Oncology, 2020)
Immunotherapy-based combinations have become standard of care in advanced renal cell carcinoma (RCC). Despite the potential for complete radiographic response, complete pathologic responses have been rarely reported. We present two cases of confirmed complete pathologic response to immunotherapy despite residual radiographic abnormalities. The first case describes a 68-year-old female with metastatic RCC who was treated with upfront pembrolizumab plus axitinib. She underwent nephrectomy after 15 doses of pembrolizumab with pathology revealing no evidence of viable tumor. To our knowledge, this is the first reported case of a complete pathologic response with pembrolizumab in metastatic RCC. The second case describes a 64-year-old female with metastatic RCC who was treated with second-line nivolumab after progression on cabozantinib. After 13 doses of nivolumab, she underwent nephrectomy with pathology revealing no evidence of viable tumor. These cases highlight the potential for scar tissue, fibrosis, and necrosis to persist radiographically after treatment with immunotherapy despite the absence of viable tumor cells.